PEMBERDAYAAN POTENSI DESA TAPAK GEDUNG UNTUK MENINGKATKAN PRODUKSI AYAM ARAB - Dewi Handayani (Universitas Bengkulu, 2018)
The purposes of the devotion activities are to provide the skill of the society in empowering the village potential for productifity of raising Arab chickens; to increase the production of Arab chickens by exploiting the natural resouces in Tapak Gedung village, the cage materials, the feed materials, and the available of human resources. Moreover, it can form a business unit that will be coordinated by a group of farmers to manage the production and product marketing of eggs, chicken meat, and chicken manure as a business for establising and develoving the independent and economically society. The method use in this devotion is by using extension activities, training, guided practice, and evaluation. In the extentsion phase, participants are given counseling about the potential of the village for raising chicken Arab. In the training and workshop phase, participants are given the material about the making of the cage, feed mabufacturing, chicken raising, and bussines development. In the direct and guided practice, participants are invited to make the cage, make the feed, and raise chickens until they can produce eggs, chicken manure, and chicken meat. Then, the product will be market and socialize to another village in Kepahiang district. From the result devotion, society has to understand how to make chicken cage and chicken feed, how to raise Arab chicken and a way of packaging and marketing of eggs Arab chickens. Societies are very enthusiastic and hope that this program can continue for the next years, and there is a serious coaching from the goverment, especially, the animal and husbandry department. The hope is there is funding from goverment for the development of larger business as efforts to improve the welfare of the society in the village. Keywords: arab chicken eggs, arab chicken production